Fear and food: Anxiety‐like behavior and the susceptibility to weight loss in an activity‐based anorexia rat model. Issue 4 (25th November 2021) - Schwenzer, Constanze; Voelz, Clara; Kogel, Vanessa; Schlösser, Anna; Herpertz‐Dahlmann, Beate; Beyer, Cordian; Seitz, Jochen; Trinh, Stefanie
Abstract: Anorexia nervosa (AN) is a severe psychiatric disorder characterized by energy restriction, low body weight, a fear of gaining weight, and often excessive physical activity. Anxiety disorders appear to constitute a major risk factor for developing AN and are the most frequent comorbidity. Here, the influence of anxiety‐like behavior prior to food restriction on increased physical activity, leading to greater susceptibility to weight loss, was tested in rats. Furthermore, the possible anxiolytic effect of starvation itself was analyzed. A chronic starvation model activity‐based anorexia (ABA) was applied to mimic physiological and behavioral characteristics of AN. During the induction of starvation and acute starvation, food intake was reduced by 70% and the rats lost 25% of their body weight, which was kept stable to imitate chronic starvation. Anxiety‐like behavior was quantified before and after chronic starvation using the elevated plus maze, based on rodents' aversion to open spaces. Anxiety‐related behavior before food restriction was associated with increased running‐wheel activity during habituation and during the induction of starvation, and predicted faster weight loss in ABA rats. Additionally, food‐restricted animals showed less anxiety‐like behavior after chronic starvation. Animals showing more anxiety‐like behavior appear to be more susceptible to weight loss, partially mediated by increased physical activity. Anxiety‐related behavior was associated with increased physical activity, which in turn was associated with more rapid weight loss. Our data let us assume that food restriction has an anxiolytic effect. These findings demonstrate the importance of considering anxiety disorders in patients with AN.